2017
DOI: 10.1021/acs.jmedchem.6b01690
|View full text |Cite
|
Sign up to set email alerts
|

Thienopyrimidinone Based Sirtuin-2 (SIRT2)-Selective Inhibitors Bind in the Ligand Induced Selectivity Pocket

Abstract: Sirtuins (SIRTs) are NAD-dependent deacylases, known to be involved in a variety of pathophysiological processes and thus remain promising therapeutic targets for further validation. Previously, we reported a novel thienopyrimidinone SIRT2 inhibitor with good potency and excellent selectivity for SIRT2. Herein, we report an extensive SAR study of this chemical series and identify the key pharmacophoric elements and physiochemical properties that underpin the excellent activity observed. New analogues have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 111 publications
2
74
0
Order By: Relevance
“…As previously described, bulky aromatic substituents are necessary to fill the so‐called “selectivity pocket” in SIRT2 . It is highly probable that the biphenyl derivatives have a similar binding pose as that of the co‐crystalized thienopyrimidinone‐based inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, bulky aromatic substituents are necessary to fill the so‐called “selectivity pocket” in SIRT2 . It is highly probable that the biphenyl derivatives have a similar binding pose as that of the co‐crystalized thienopyrimidinone‐based inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…For ab etter understandingo ft he experimentally determined IC 50 values and their structural foundation, we used ac om-bined dockinga nd molecular dynamics approach for predicting possible binding modes.A ll compounds were docked to the substrate pocket of SIRT2 with at hienopyrimidinone-based inhibitor 19 [23] as template and visually inspected.T he docking poses of 16 q were passed to molecular dynamics simulations for post-processing and refinement. The ligand movements were monitored by its RMSD value to ensure as table final bindingp ose (see the Supporting Information).…”
Section: Computational Chemistrymentioning
confidence: 99%
“…In the crystal structures of sirt1, it was shown that substrates make H-bond interactions with the backbone of a conserved valine residue (sirt1 numbering Val412) which is crucial for the correct orientation of the acyl-lysine in the active site [44]. In case of sirt2, we first examined the binding interactions of the native ligands including both the peptide substrates, the cofactor fragments and the co-crystallized inhibitors with the protein [31][32][33][34][35][36][37][38][39][40][41][42][43]. In the hit selection process, a special importance was given to compounds that were able to interact with residues Phe234, Phe235, Phe190 and Glu237 in the catalytic pocket.…”
Section: Docking Scoring and Hit Selectionmentioning
confidence: 99%
“…Within the last two decades, several sirt1 and sirt2 crystal structures have been solved in both apo and holo forms [31][32][33][34][35][36][37][38][39][40][41][42][43]. Ternary structures of sirt1 and sirt2 in complex with cofactor analogues, peptide-based and structurally diverse inhibitors revealed a high conformational flexibility in the catalytic pocket, especially in the extended C-pocket region.…”
Section: Introductionmentioning
confidence: 99%
“…Some thieno [2,3-d]pyrimidin-(4)-ones act as selective phosphodiesterase inhibitors for the treatment of inflammatory diseases, 8,9 antagonists of the glutamate receptors 10 whereas others were identified as highly selective SIRT2 inhibitors. 11,12 Owing to their growing use in compounds of therapeutic importance, the synthesis of various thienopyrimidinone-based molecules has been actively pursued in the last past decade and studied in detail, leading to several new developments. 3,13,14 This skeleton is usually obtained by condensation and ring closure from various 2,3-substituted thiophenes such as Gewald's amide, 15 2-aminothiophene-3-carbonitrile, 16 3-carbethoxy-2-phenylthioureathiophene, 17 2-aminothiophene-3-carboxylic ester.…”
Section: Introductionmentioning
confidence: 99%